Childhood Trauma Predicting Attachment Style In Young Adults - Chisom E. Ogbonnaya; Comfort S. Atota; Emmanuel E. Uye (Science: Indonesian Journal of Science, 2026)
This study examines the predictive role of childhood trauma on attachment styles in young adults. Cross-sectional survey was utilized while purposive sampling technique was used to select the study population. Data were collected from 278 participants using validated questionnaires and analyzed using simple linear regression to test a hypothesis which was accepted at p <.001 level of significance. The result demonstrates that childhood trauma significantly influenced attachment style among study participants, R2 = .219, F (1, 276) = 28.27, p < .001. Furthermore, the result reveals that childhood trauma independently predicted attachment style among study participants (β = .468, t = 5.32, p < .001).  The study concludes that childhood trauma is a robust predictor of attachment style in the population of study. The study recommends mental health practitioners should integrate trauma-informed and attachment-based approaches in therapy to address unresolved childhood experiences among young adults.